Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1975
DOI: 10.1111/j.1365-2222.1975.tb01839.x
|View full text |Cite
|
Sign up to set email alerts
|

Half‐life of CINH in hereditary angioneurotic oedema (HAE)*

Abstract: Summary The half‐life of125I labelled CINH was determined in patients with HAE and normal controls. There was no significant difference between these two groups. The half‐life in the HAE patients was 67.7 hr ± 4.9 hr (s.d.) and in the normals 64 hr± 1.4 hr (s.d.). This finding is consistent with a defect in synthesis as an explanation of the low serum C1NH levels in HAE patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

1976
1976
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…Patient‐dependent variability has been reported regarding the half‐life of functional C1‐INH activity 20 . Kodama and colleagues 20 reported a mean half‐life for a pC1‐INH of 5.62 days, whereas Brackertz and colleagues 21 found the half‐life for a radiolabeled C1‐INH preparation in HAE patients was 67.7 hours, compared with 64 hours in healthy controls. In the study by Brackertz and colleagues, the functional activity of the C1‐INH preparation used represented only 38% of what is standard, indicating that some denaturation may have taken place, leading to an initially rapid disappearance of C1‐INH from the vascular compartment 21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient‐dependent variability has been reported regarding the half‐life of functional C1‐INH activity 20 . Kodama and colleagues 20 reported a mean half‐life for a pC1‐INH of 5.62 days, whereas Brackertz and colleagues 21 found the half‐life for a radiolabeled C1‐INH preparation in HAE patients was 67.7 hours, compared with 64 hours in healthy controls. In the study by Brackertz and colleagues, the functional activity of the C1‐INH preparation used represented only 38% of what is standard, indicating that some denaturation may have taken place, leading to an initially rapid disappearance of C1‐INH from the vascular compartment 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Kodama and colleagues 20 reported a mean half‐life for a pC1‐INH of 5.62 days, whereas Brackertz and colleagues 21 found the half‐life for a radiolabeled C1‐INH preparation in HAE patients was 67.7 hours, compared with 64 hours in healthy controls. In the study by Brackertz and colleagues, the functional activity of the C1‐INH preparation used represented only 38% of what is standard, indicating that some denaturation may have taken place, leading to an initially rapid disappearance of C1‐INH from the vascular compartment 21 . Using fresh plasma administered to an HAE patient during an attack, and determining the concentration of C1‐INH by radial immunodiffusion for 6 days, the same group observed a half‐life of 39 hours 21 .…”
Section: Discussionmentioning
confidence: 99%
“…As a serine protease inhibitor, the main function of C1-INH is to regulate the activity of serine proteinases. The biologic half-life of C1-INH in healthy subjects is 64 ± 1.4 hours suggesting that treatment every 3 days is necessary to restore C1-INH levels24 (Figure 1a). …”
Section: Pharmacology and Pharmacokineticsmentioning
confidence: 99%
“…In a number of these studies [15][16][17] the apparent disappearance rate constant (k d ) rather than the true fractional catabolic rate constant for the disappearance of C1-INH from plasma was determined. For instance, Brackertz et al 16 found a biphasic disappearance of injected C1-INH in control subjects and reported a plasma half-life of 64 hours for the final slow disappearance phase from 3 to 8 days after injection. However, the corresponding apparent disappearance rate constant k d ϭ (ln2)/64 ϭ 0.011 h Ϫ1 also incorporates the return of extravascular C1-INH to plasma, which suggests that the FCR would be even lower than 0.011 h Ϫ1 .…”
Section: Estimation Of Fcr: Comparison With Data From Literaturementioning
confidence: 99%
“…For instance, Brackertz et a1 16 found a biphasic disappearance of injected Cl-INH in control subjects and reported a plasma half-life of 64 hours for the final slow disappearance phase from 3 to 8 days after injection. However, the corresponding apparent disappearance rate constant kd = (ln2)/64 = 0.011 h-1 also incorporates the return of extravascular Cl-INH to plasma, which suggests that the FCR would be even lower than 0.011 h-1.…”
Section: Estimation Of Fcr: Comparison With Data From Literaturementioning
confidence: 99%